ANALISIS KESALAHAN PENYELESAIAN SOAL URAIAN ULANGAN AKHIR SEMESTER (UAS) GASAL MATEMATIKA SISWA SMP NEGERI 2 NGUTER - endang handaripraba (Universitas Veteran Bangun Nusantara, 2020)
The objective of this research is to identify the mistakes made by students in solving final exam problems of 2017/2018 in odd semester so that similar errors can be minimized for later learning achievement of mathematics can be improved. This is qualitative research. Data collection techniques in this study are interviews and documentation. The results of the study were: (1) malpractice procedure 16%, including low error rate, (2) response level conflict level of 28%, including medium error rate, and (3) hierarchical problem skills (skills hierarchy problem) of 5.56% then including the error rate is very low.